Affordances and Constraints of Implementing Lesson Study for Teachers’ Professional Development: A Review - JIMMY KIHWELE (African Journal of Teacher Education, 2020)
Lesson Study (LS) has been adopted worldwide as a research tool for teachers who teach the same subjects to cooperate in identifying problems, planning a lesson, teaching that lesson and coming up with solutions to the problem identified. This helps them grow professionally. This study is a review of approaches to implementing LS in different places, of opportunities that the use of LS provides, and of constraints on its effectiveness and sustainability. In this study, 30 published research articles were thoroughly studied and analyzed so as to answer three key questions that serve as its underpinning. The findings show that the methods used to implement LS vary in many places. However, in several cases, LS practitioners try to implement the original structure of LS as it was implemented in Japan in the 1960s. The findings show that LS affords more pedagogical opportunities than constraint: teachers learn new professional skills and knowledge and they improve their understanding of the subject matter and change their attitudes, beliefs and views on collaborative working.